Pengaruh Video Edukasi Tablet Tambah Darah dan Gizi Ibu Hamil terhadap Pengetahuan, Kepatuhan, dan Kadar Hemogblobin - Erowati, Dewi; Yolahumaroh, Yolahumaroh; Marlina, Yessi (Jurnal Kesehatan Komunitas, 2023)
Background: Pregnancy is a very important period, the state of the mother and fetus are related to one another. While pregnant women are often found to have iron deficiency anemia. One of the efforts to overcome the problem of anemia in pregnant women is by giving iron supplements. However, in Riau Province pregnant women who received FE3 decreased, namely in 2018 as much as 79% decreased to 65% in 2019. Therefore, an educational method is needed to increase knowledge, and adherence to taking iron supplements, and hemoglobin (Hb) levels in pregnant women. Objectives: To increase knowledge and adherence of taking iron supplements and hemoglobin (Hb) levels in pregnant women. Methods: This study is a pre-experimental study with one group pretest and post-test to evaluate the effect of nutrition education with video media on knowledge, adherence to taking iron supplements, and Hb levels in late-trimester pregnant women. The educational videos include material on the importance of taking iron supplements, how to consume them, and balanced nutrition for pregnant women. Result: There is a statistically significant difference between the knowledge and the adherence of pregnant women taking iron supplements before and after treatment or intervention with a significance value of 0.000 (<0.05). Changes in Hb levels before and after treatment or intervention in the form of Educational Video for Iron Supplements (TTD) and Nutrition for Pregnant Women did not show a statistically significant difference with a significance value of 0.085 (> 0.05).Conclusion: Educational videos on iron supplements and nutrition for Pregnant Women affect knowledge and adherence of pregnant women taking iron supplements.